(untitled) - Seagrave, Sterling (New York, 1995)
An examination of the complex web of Chinese operations dominating the Far East's booming economies is part economic analysis, part history, and part cautionary tale that encompasses murder, betrayal, corruption, and syndicates and features kingmakers, emperors, generals, spies, and pirates.
Keywords: Investments, Chinese,Đầu tư, Trung Quốc; History,Lịch sử; Pacific Area,Thái Bình Dương